PERANCANGAN RACI MATRIX UNTUK MENGELOLA STAKEHOLDERS DALAM STUDI KASUS PROYEK PT XYZ - Fauzan Rezki Maulana (2023)
PT XYZ is a company engaged in the Event Organizer field in collaboration with the Ministry of Transportation of the Republic of Indonesia. Based on the results of observations through interviews, field observations, and studies of company documents in the PT XYZ event organizer case study, it was found that there were projects that experienced delays and cost overruns. After being analyzed, the authors concluded that this was caused by poor integration about roles and responsibilities in every stakeholders. Because of this, one method that is suitable to be used and implemented is the RACI Matrix. This study aims to design the RACI Matrix and Job Description List in accordance with project management guidelines. For work assignments in the PT XYZ case study project, the results of the RACI Matrix design show nine stakeholders grouped into four classifications according to the RACI components arranged based on the responsibilities of each stakeholder towards the project. The results of the Job Description design show five stakeholders who are further explained about their job descriptions. And the results of the Gantt Chart design show the scheduling for all job descriptions.